Komunikasi Lintas Kebudayaan dan Potensi Masalah-Masalah yang Timbul - Rifka Pratama (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
In the midst of the intensive cross-cultural interactions today, there is a potential for misunderstanding within the ongoing communication process. If this continues, it can lead to disharmony. The confluences of two or more cultures have always the potential for misunderstanding with various reasons. This paper describes the potential problems around the cross-cultural communication. These problems are classified into two types, namely those related to the cultural practices and the mental images around and those related to the linguistic aspects.